Physical education class can improve acute inhibitory control in elementary school students - Franco-Alvarenga,Paulo Estevão (2019)
Abstract Aim: The aim of the study was to analyze the impact of a based-team sports physical education class on inhibitory control of elementary school children. Methods: Were selected 29 elementary school students (13 boys and 16 girls; 10.7 ± 0.7 years old; 43.2 ± 8.2 kg weight; 147 ± 5 cm height). Participants were submitted to a 50-minute sports-based physical education class performed at moderate intensity. Inhibitory control was measured before and immediately after the end of the physical education class by the Stroop Test. Results: Results indicate that the variables derived from Stroop Test performance overall reaction time were significantly reduced after the physical education class (p < 0.05). Conclusion: These results suggest that a 50-minute sports-based physical education class performed at moderate intensity elicited a significant improvement on the inhibitory control elementary school students.